2018
DOI: 10.1021/acs.bioconjchem.7b00816
|View full text |Cite
|
Sign up to set email alerts
|

Filomicelles Deliver a Chemo-Differentiation Combination of Paclitaxel and Retinoic Acid That Durably Represses Carcinomas in Liver to Prolong Survival

Abstract: Drug resistance and relapse is common in cancer treatments with chemotherapeutics, and while drug combinations with naturally occurring, differentiation-inducing retinoic acid (RA) provide remission-free cures for one type of liquid tumor, solid tumors present major problems for delivery. Here, inspired by filoviruses that can be microns in length, flexible filomicelles that self-assemble from an amphiphilic block copolymer (PEG−PCL) are shown to effectively deliver RA and paclitaxel (TAX) to several solid tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 56 publications
0
15
0
1
Order By: Relevance
“…PEG is the most popular choice for the hydrophilic block. Polyethylethylene [60], polybutadiene [61], polydimethylsiloxane [62], polycaprolactone (PCL) [63], PLA [64], PLGA [65], and polystyrene [66] are some of the polymers that have been used as hydrophobic blocks. Beside molecular weight (chain size), other properties that can be altered include charge/zeta potential, polydispersity, and crystallinity.…”
Section: Motivations Behind a Polymeric Approach To Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations
“…PEG is the most popular choice for the hydrophilic block. Polyethylethylene [60], polybutadiene [61], polydimethylsiloxane [62], polycaprolactone (PCL) [63], PLA [64], PLGA [65], and polystyrene [66] are some of the polymers that have been used as hydrophobic blocks. Beside molecular weight (chain size), other properties that can be altered include charge/zeta potential, polydispersity, and crystallinity.…”
Section: Motivations Behind a Polymeric Approach To Nanoparticlesmentioning
confidence: 99%
“…Paclitaxel acts as the cytotoxic agent here, while the ‘differentiative’ agent aims to irreversibly differentiate surviving cells into a quiescent state, incapable of initiating tumor regrowth [146]. Combination of Paclitaxel with Retinoic acid—a metabolite of Vitamin A that possesses differentiative properties—reduced resistance and relapse in liver and lung tumor xenografts [63]. Cylindrical micelles coloaded with retinoic acid and paclitaxel was found to be more cytotoxic in vitro.…”
Section: Delivering Combination Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, early studies have shown that while crawling on the scars, well-spread cells polarize more with greater persistence (several hours longer) along the scar's long axis than less spread cells, suggesting that responses for spreading and non-spreading cells could be divergent. Mouse liver cancer cells (Dox-inhibitable MYC-expressed EC4 cells (Anderton et al, 2017;Nair et al, 2018)) cultured on stiff substrate exhibit more nuclear spreading and higher proliferation (4N population) than that on soft matrices (Fig. 2B).…”
Section: Sample Studies Of Nucleus Utilizing Mmmsmentioning
confidence: 99%